Advances in Cyclosporiasis Diagnosis and Therapeutic Intervention - Li, Junqiang; Cui, Zhaohui; Qi, Meng; Zhang, Longxian (Frontiers in Cellular and Infection Microbiology, 2020)
Cyclosporiasis is caused by the coccidian parasite Cyclospora cayetanensis and is associated with large and complex food-borne outbreaks worldwide. Associated symptoms include severe watery diarrhea, particularly in infants, and immune dysfunction. No vaccine is available but early detection and treatment of cyclosporiasis can result in a favorable clinical outcome. Clinical diagnosis is based on cardinal clinical symptoms and conventional laboratory methods, which usually involve microscopic examination of wet smears, staining tests, fluorescence microscopy, serological testing, or DNA testing for oocysts in the stool. Detection in the vehicle of infection, which can be fresh produce, water, or soil is helpful for case-linkage and source-tracking during cyclosporiasis outbreaks. Treatment with trimethoprim-sulfamethoxazole (TMP-SMX) can evidently cure C. cayetanensis infection. Ciprofloxacin is less effective than TMP-SMX but it is suitable in patients who are intolerant to sulfonamide drugs. Nitazoxanide is an alternative treatment option in patients with a sulfa allergy or in cases where ciprofloxacin has failed. More epidemiological research investigating cyclosporiasis in humans should be conducted worldwide, to achieve a better understanding of its characteristics in this regard. It is also necessary to establish in vitro and/or in vivo protocols for cultivating C. cayetanensis, to facilitate the development of rapid, convenient, precise, and economical detection methods for diagnosis, as well as more effective tracing methods. Due to the ongoing globalization of the human food supply, this apicomplexan parasite is prevalent in both endemic regions that produce food and the non-endemic regions that food is exported to. As well as being a burden on the health of individual humans, cyclosporiasis is a global public health concern.